KRISTALISASI LIKOPEN DARI BUAH TOMAT (Lycopersicon esculentum) MENGGUNAKAN ANTISOLVENT - Deviana Christianty, Sola Fide Gavra, Zuhrina Masyithah (Universitas Sumatera Utara, 2015)
Studies on the utilization of lycopene had been conducted to determine the effect of comparison feed and solvent (F/S) and the addition of methanol for extraction of lycopene from tomatoes using mixture solvent of hexane:ethyl acetate (1:1) followed by crystallization antisolvent. In this research, ripe tomatoes juice was used with volume 150 ml. Lycopene extract was obtained through extraction method at temperature of 70 °C and the stirring speed 7 rpm. The other method was by the addition of methanol as antisolvent for crystallization. As for changing variable in this study were a comparison of feed and solvent (F/S) 1:2; 1:2.5; 1:3; 1:3.5; 1:4 and 1:4,5, and the volume of methanol as antisolvent were 50 ml, 100 ml, 150 ml and 200 ml. The results of this research about influence of feed and solvent to lycopene yield extracted obtained at the optimum condition 1:4 with a volume of 200 ml antisolvent. Whereas the influence about addition of methanol as antisolvent as an agent of precipitation and maximum condition occurs on volume of 200 ml. Wavelength analysis of C=C linkage with Fourier Transform Infrared (FT-IR) detected at wavenumber 1519,91 cm-1, CH2 linkage detected at wavenumber 1446,61 cm-1, R-CH=CH-R linkage detected at wavenumber 979,84 cm-1. While, C-C and C-CH linkage detected at wavenumber 1138 and 1373,32 cm-1.